KAUM INTELEKTUAL DALAM POLITIK PERTAMBANGAN - Djaja Hendra; Endriatmo Soetarto; Arya H Dharmawan; Bambang Purwanto (Jurnal Ilmiah Mimbar Demokrasi, 2012)
This research about agrarian social change in Bangka. The method in this study uses structural Gramscian perspective and critical theory approach. The results of research has showed the role of intellectuals in the social change process. Its related to political dynamic in this area. After the new Order Era, the position of the intellectual very importance, especially in moving of mass aspiration. In this context, these change are realted to the role of the intellectual as a social entity forming the state and civil society well that the New Orde era and before the for the political leadership through organic intellectual actor. In the pos New Orde era more emphasizes the intellectual and moral leadership.